Mobility, Elites and Education in French Society of the Second Empire - Harrigan, Patrick J. (Patrick Joseph), 1941- (Book collections on Project MUSE., 1980)
Based on a unique historical source, this book examines the social origins, career expectations, and first jobs of 28,000 students in the "elitist" French secondary schools of the 1860s. Using sophisticated statistical analysis as well as conventional historical sources, the work concludes that schooling reached a wider audience than has been so far believed and that substantial social mobility occurred within the school system, but that family background, rather than educational factors, directed students' career aspirations and achievements. It also argues that although education expanded in urban, industrialized areas, mobility did not increase in these areas. A final chapter reconsiders nineteenth-century thought concerning education in the light of findings about the social effects of schools